Use of social marketing in diabetes control in the UAE context. (2nd January 2018) - Samad, Nayyer; Samad, Nasreen; Abdallah, Salam
Abstract: Objective : This study aims to provide information on the perceptions of and practices used for diabetes in the UAE with the view to generate evidence-based strategic guidelines for future programs. Method : A multi-method approach was used. It included a survey to collect data on the current level of awareness, attitudes, and behaviors among diabetic and non-diabetic samples in Al Ain, UAE. We reviewed the literature on the social marketing framework and its suitability to diabetes control and prevention programs. Results : Knowledge about the disease was generally low. The level of awareness among members of the diabetic group, however, was found to be slightly better than that of their non-diabetic counterparts. Practices related to diabetic care were mixed. Social marketing is a recognized intervention method for influencing behavior and has been used effectively in various health programs worldwide. Conclusions : Low awareness of diabetes would further increase the number of diabetes and diabetes-related complications in future years, putting an enormous burden on the healthcare system. A social marketing intervention focusing on behavioral change can offer an effective solution.